Influence of Fuel Type Gasoline For Power, Torque, And Emissions On 4 Stroke Motorcycles - Miki Tri Susanto; Andrizal Andrizal; Martias Martias (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2019)
Various assumptions circulating in the community about the use of fuel types on motorcycles, among others; First use of a conventional motorcycle with a low compression can help clean the burn chamber, improve the performance of the engine, and no difference the perceived premium fuel users have on the EFI motorcycle with the compression Lower. The angapan caused the user to prefer Premium fuel due to a more economical price. This study was conducted to determine the influence of fuel usage on machine performance with multiple criteria. There is a treatment applied to the research object, so to get the desired data on this research using the experimental method. The resulting power drop occurred on the use of premium and pertalite fuels when compared with the power generated on the use of first fuel. The biggest power decline occurred in the comparison of power between first fuel with premium with a large decrease of 4.32%.